REDESCRIPTION AND NEW DISTRIBUTIONAL RECORDS OF XENORHYNCHIUM NITIDULUM (FABRICIUS) (HYMENOPTERA : VESPIDAE : EUMENINAE) FROM VARIOUS STATES OF INDIA - GIRISHKUMAR, P.; KISHORE, LAMBERT (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2011)
The species Xenorhynchium nitidulum (Fabricius) is recorded for the first time from Himachal Pradesh, Jharkhand, Maharashtra and Pondicherry and redescribed here. Xenorhynchium Initidulum (Fabricius), Himachal Pradesh, Jharkhand, Maharashtra, Pondicherry.